Analisis Masa Simpan Jenang Labu Siam Berpotensi Sebagai Produk Oleh-Oleh Baru - Putri Yanesya; Betti Janusari; Zenna Azerine Kalista; Dini Junita (Jurnal Akademika Baiturrahim Jambi, 2020)
Jenang, or what is often called dodol, slab, or gelamai, includes dense, chewy, half-processed products. Jenang, which was innovated from chayote, has a relatively short shelf life, which is only able to survive 3-5 days at room temperature (27ºC). Therefore, a good packaging is needed that can extend the shelf life of one of them is edible coating, which is the packaging of edible materials. Edible coating is one of the efforts that can be done to maintain the quality of a food. The purpose of this study was to determine the quality and estimation of chayote with and without edible jenang based on physical, chemical, and microbiological parameters. In this study using the analysis of water content, peroxide numbers, and total microbes and using the edible dip method. From the research it can be seen that the chayote jenang based on physical quality in edible samples can maintain the water content so that the texture remains elastic compared to without edible until the 15th day. Based on the chemical quality in jenang squash with edible, oxidation only occurred after storage on the 22nd day. Microbiological quality in the conjoined pumpkin jenang coated with edible or without edible was overgrown with a total amount of yeast mold ≥300,000 Cfu / g.